Analisis Kemampuan Komunikasi Matematis Siswa Dalam Menyelesaikan Soal Cerita Ditinjau Dari Gaya Belajar Siswa - Teguh Imanda Prastia; Sri Subarinah; Nurul Hikmah (Lembaga Bale Literasi, 2025)
Mathematical communication is a fundamental skill that students must possess and master to facilitate their mathematics learning activities. This study aims to describe the mathematical communication skills of students with visual, auditory, and kinesthetic learning styles in solving word problems related to the straight-line equation. This research is a qualitative descriptive study. The subjects were eighth-grade students at SMPN 6 Mataram. To select the subjects, a learning style questionnaire was administered to three classes to determine one class that would be given a mathematical communication skills test. The study involved 33 students, consisting of 14 students with a visual learning style, 10 students with an auditory learning style, and 9 students with a kinesthetic learning style. The instruments used were a questionnaire, a test, and an interview guide. The data analysis techniques were data reduction, data presentation, and conclusion drawing. In general, students with visual, auditory, and kinesthetic learning styles demonstrated a moderate level of mathematical communication skills. Students with a visual learning style were only able to complete two indicators. Students with an auditory learning style could complete three indicators, but not fully. Students with a kinesthetic learning style were only able to complete two indicators.